Mechanisms for Forming Digital Literacy of College Teachers under the Digital Transformation of Education - Wu, Huabin; Mao, Xinjie; Xu, Xiangdong (International Journal of Scientific Research and Management (IJSRM), 2024)
With the rapid development of information technology, the digital transformation of education has become an important trend of global higher education reform. In this context, the digital literacy of higher education teachers is not only related to their personal career development, but also a key factor affecting the quality of teaching and the development of students' abilities. Several problems have been identified through the research study, such as unbalanced distribution of resources, limited opportunities for professional development, missing evaluation system, insufficient social interaction and cooperation, and low self-efficacy, which collectively affect the formation of digital literacy among college teachers. Based on this, this study puts forward a series of recommendations, such as exploring the digital literacy hierarchy of college teachers under the digital transformation of education, clarifying the direction of cultivating digital literacy of college teachers under the digital transformation of education, and constructing a cultivation mechanism of multi-party collaboration and cooperation, with a view to promoting the enhancement of the digital literacy of college teachers, and then promoting the digital transformation of higher education.